Zoning of the agricultural potential of the soil at a cultivation area in the region "Zona da Mata" of Pernambuco - Barbosa Neto, Manuella Vieira; Araújo, Maria do Socorro Bezerra de; Araújo Filho, José Coelho de (Sociedade & Natureza, 2017)
The basin of the river Natuba is an important vegetable production polo for supplies, especially to the metropolitan area of Recife. Rational planning of the land use in the basin is needed to ensure the conser - vation of this resource. This study aimed to carry out the zoning of the agricultural potential of the land in the middle course of the river Natuba basin - PE, considering the average (management B) and high (management C) technologies application. The analysis was based on the criteria: fertility deficiency, water deficiency, excessive water, susceptibility to erosion and impediments to mechanization. The results indicated that the most recommended conservationist ways of land use are planted crops and pasture, narrowly, in the management B. The possibility of land use in management C is limited to the unit of Latosols located in top areas, and Gleysols in the environment of floodplain. The current use practiced in the studied area complies only partly with the agricultural potential of the land. On the steep slopes, the intensive irrigated agriculture doesn’t combine to the agricultural potential use. Management techniques related to conservationist ways of soil use should be deployed throughout the area.